Advancements in the Association between a Body Shape Index and Atherosclerosis - CHEN Xiaoqian, LI Lihua (Zhongguo quanke yixue, 2024)
A body shape index (ABSI) is a novel anthropometric index derived by specific algorithms based on measurements of height, weight, and waist circumference. Central obesity has become more important for predicting the occurrence and mortality of cardiovascular events with the increasing number of overweight and obese people. Obesity contributes to the development of cardiovascular diseases such as atherosclerosis, hypertension, coronary heart disease and even death by stimulating the production of inflammatory factors that induce chronic inflammatory responses, insulin resistance, metabolic disorders and oxidative stress pathways. ABSI is strongly related to abdominal obesity and can predict atherosclerosis in some populations, but it is also affected by population characteristics, such as the difference in the correlation between ABSI and atherosclerosis in populations of different regions, genders and ages. It is of great significance for early identification of high-risk populations and rational prevention and treatment of cardiovascular diseases to clarify the relationship between ABSI and atherosclerosis.